Overview of tigecycline and its role in the era of antibiotic resistance - Rossi,Flávia (2006)
The increasing antimicrobial resistance found in the many clinically important species of bacteria that commonly cause serious and life-threatening diseases presents a difficult challenge for clinicians, especially when an appropriate initial therapy must be chosen. New antibiotics are urgently needed to address the formidable issues associated with infections caused by vancomycin-resistant enterococci (VRE), methicillin-resistant Staphylococcus aureus (MRSA), penicillin-resistant Streptococcus pneumoniae and multidrug-resistant Gram-negative bacteria. The need for new antibiotics that effectively resist antimicrobial mechanisms of resistance has become paramount. Tigecycline is a new antimicrobial agent; it is the first in a new class of antibiotics, the glycylcyclines, with properties conferring the ability to overcome many common resistance mechanisms, thus allowing the use of tigecycline for many serious and life-threatening infections for which the use of other antibiotics is no longer appropriate. Tigecycline is a novel expanded spectrum antibiotic that appears poised to meet the latest bacterial challenges facing clinicians, including the serious and life-threatening infections caused by highly resistant bacteria. Tigecycline, moreover, appears to hold promise as a new, versatile antibiotic that can be chosen for empirical therapy, even as a single agent, for initial therapy of many clinically important infections.